Percentage volume of delayed kinetics in computer-aided diagnosis of MRI of the breast to reduce false-positive results and unnecessary biopsies. Issue 12 (December 2020) - Ha, T.; Kang, D.K.; Kim, T.H.
Abstract : AIM: To investigate the best cut-off percentage volume of delayed kinetics using magnetic resonance imaging (MRI) with computer-aided diagnosis (CAD) to reduce unnecessary biopsies in patients with newly diagnosed breast cancer. MATERIALS AND METHODS: Between January 2017 and December 2018, 94 malignant and 56 benign masses were analysed using MRI CAD. All malignant and benign masses measured <2 cm and were confirmed histopathologically. The optimal cut-off values for washout, plateau, and persistent components were determined using the maximum Youden Index. The positive predictive value (PPV) was analysed using morphological descriptors and combining the percentage volume of delayed kinetics. RESULTS: The area under the curve (AUC) was highest at ≤73% persistent component (AUC=0.759). In the subgroup analyses of masses <1 cm, the AUC was highest a plateau of >26% (AUC=0.697). When the persistent ≤73% criterion was applied to the lesions of C4a, the positive predictive value (PPV) increased from 61.9% to 72.44% with reduced false-negative cases and when applied to the lesions of C4a and C4b, the PPV increased from 61.9% to 78.1% with slightly increased false-negative cases. For subcentimetre lesions, the PPV increased from 46.77% to 54.72% with the same number of false-negative cases, when a plateau of >26% was applied to C4a, and the PPV increased from 46.77% to 61.36% with five false-negative cases when applied to C4a and C4b. CONCLUSION: The percentage volume of delayed kinetics has the potential to improve the PPV of breast MRI. When suspicious masses <2 cm do not show ≤73% persistence, follow-up rather than biopsy could be considered; however, to avoid increasing false-negative cases, delayed kinetic information should be used with caution and accurate margin assessment is essential. Highlights: Percentage volume of delayed kinetics has the potential to improve the PPV of breast MR imaging. When suspicious mass smaller than 2cm does not show ≤73% persistent, follow-up rather than biopsy can be considered. For subcentimeter masses, persistent ≤ 73% or plateau > 26% could be effective.